The energy model of insulin resistance: A unifying theory linking seed oils to metabolic disease and cancer - Shanahan, Catherine (Frontiers in Nutrition, 2025)
The problem of insulin resistance has exploded in recent decades, from practically nonexistent in 1950, to nearly ubiquitous today. Despite this, the dietary origins of insulin resistance remain elusive. Many have identified the Western Diet, focusing on saturated fat. However, population-scale consumption data shows that our consumption of saturated fat has remained unchanged, while our consumption of polyunsaturated fats has increased by more than 300%. This paper discusses the primary source of those polyunsaturated fatty acids (PUFA), a collection of eight chemically similar refined, bleached, and deodorized (RBD) seed oils, i.e., soy and canola, that now, together, represent the number one source of calories in the United States today, or approximately 30 percent of the average person’s daily intake. The Energy Model of Insulin Resistance hypothesizes that RBD seed oil consumption can promote cellular oxidative stress, forcing cells to change their fueling strategy to reduce oxidative stress. This is accomplished by increasing aerobic glycolysis to minimize fat oxidation. Observed in both cancerous and insulin resistance cells, aerobic glycolysis is also known as the Warburg Effect. While beneficial to individual cells, at the whole-organism level, it disrupts intravascular glucose homeostasis, ultimately elevating insulin and counter-regulatory hormones (CRH) simultaneously. CRH oppose the insulin signal, leading to the phenotype of insulin resistance. In summary, the Energy Model of Insulin Resistance provides a framework for understanding that the primary metabolic deficit in people with insulin resistance may not be abnormal insulin signaling, but rather an abnormally increased metabolic demand for sugar. If correct, this would elucidate the mitochondrial origins of the Warburg Effect and suggest that avoiding RBD oils represents an important and understudied dietary strategy for addressing insulin resistance and cancer.